När åldern skiljer oss åt - Gordon Jarneskog,Amanda (2025)
This thesis examines the relationship between age differences in marriage and spouses' reported life and family satisfaction, both at international and regional levels. The analysis is based on cross-sectional OLS regressions, using various model specifications and allowing the relationship to differ depending on whether the husband or the wife is older. The results indicate that age differences between spouses are associated with variations in reported satisfaction. However, the strength and direction of these associations differ. The most notable finding is that the relationship varies significantly across regions. This variation may help explain why previous research has yielded inconsistent and often contradictory results and conclusions. A key contribution of this study is the identification of regional factors as important mediators in the relationship between spousal age gaps and individual satisfaction outcomes.
Keywords: åldersskillnad; äktenskap; livstillfredsställelse; familjetillfredsställelse; makar